The quality of measles outbreak investigation report, how can it bridge the gap and help to fulfill the goal of measles elimination? - Elham Rahimi; Ebrahim Ghaderi; Ehsan Mostafavi; Manoochehr Karami (BMC Infectious Diseases)
Abstract Background Preparing a precise report of disease outbreak investigation is an important step to share the acquired experiences about causes of outbreaks and control measures for control and prevention of current and further outbreaks. Objective Assessing the quality of published reports of measles outbreak investigation. Method Three databases including PubMed, Web of Science, and Scopus were systematically searched to retrieve studies published between 2005 and 2022 on measles outbreak investigation reports. Data were elicited using inclusion criteria and assessing the guidelines for outbreak investigation reports. The results for mentioning each item in studies were reported by percentage. Result Sixty-four studies were assessed for the quality of measles outbreak investigation reports. Studies encompass a broad span of geographic areas. Funding revealed that outbreak investigation details are reported in most studies but some of them like type of study(37.5%), control/ unexposed selection/definition(18.75%), investigation team(10.93%), statistical test(32.81%), and symptoms of disease in cases(18.75%), are poorly reported. On the other hand, variables like description of the problem(89.07%), laboratory methods(84.38%), and feasible recommendations(95.32%), are highly reported. Conclusion Outbreak Investigation and appropriate reporting are a pilar of measles elimination program. This study highlights significant limitations in the reporting of measles outbreak investigations, including incomplete reporting of key variables. To improve the quality of outbreak reports, this study offers some suggestions, such as adopting standardized reporting guidelines and providing training courses for investigators.